2017
DOI: 10.1038/s41598-017-14094-5
|View full text |Cite
|
Sign up to set email alerts
|

Combined TDDFT and AIM Insights into Photoinduced Excited State Intramolecular Proton Transfer (ESIPT) Mechanism in Hydroxyl- and Amino-Anthraquinone Solution

Abstract: Time-dependent density functional theory (TDDFT) and atoms in molecules (AIM) theory are combined to study the photoinduced excited state intramolecular proton transfer (ESIPT) dynamics for eight anthraquinones (AQs) derivatives in solution. The calculated absorption and emission spectra are consistent with the available experimental data, verifying the suitability of the theory selected. The systems with the excited-state exothermic proton transfer, such as 1-HAQ, 1,5-DHAQ and TFAQ, emit completely from trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 78 publications
3
13
0
Order By: Relevance
“…S4. A similar excited state rearrangement is observed for the closely related compound 1,8-dihydroxy-9,10-anthraquinone (chrysazin, an oxidation product of A) as reported by Smulevich and coworkers (Smulevich et al, 1987;Marzocchi et al, 1998) and recently studied theoretically by Mohammed et al (2014) and by Zheng, Zhang & Zhao (2017).…”
Section: Excited State Intramolecular Proton Transfer (Esipt)supporting
confidence: 81%
“…S4. A similar excited state rearrangement is observed for the closely related compound 1,8-dihydroxy-9,10-anthraquinone (chrysazin, an oxidation product of A) as reported by Smulevich and coworkers (Smulevich et al, 1987;Marzocchi et al, 1998) and recently studied theoretically by Mohammed et al (2014) and by Zheng, Zhang & Zhao (2017).…”
Section: Excited State Intramolecular Proton Transfer (Esipt)supporting
confidence: 81%
“…A similar excited state rearrangement is observed for the closely related compound 1,8dihydroxy-9,10-anthraquinone (chrysazin, an oxidation product of A) as reported by Smulevich and coworkers (Smulevich et al, 1987;Marzocchi et al, 1998) and recently studied theoretically by Mohammed et al (Mohammad et al, 2014) and by Zheng et al (Zheng, Zhang & Zhao, 2017).…”
Section: Excited State Intramolecular Proton Transfer (Esipt)supporting
confidence: 79%
“…The normal and twist conformations from the S 0 and S 1 states of the AYAAQs derivatives (Figure ) and the AAQ dye (Figure ) are optimized using the CAM-B3LYP/TD-CAM-B3LYP/6-31G­(d,p)/PCM/acetonitrile level. There is no discussion of the proton transfer conformations (Supporting Information) in this article, owing to that the intramolecular proton transfer reaction of AYAAQs has been widely investigated before. The corresponding primary structural parameters of AYAAQs and AAQ are summarized in Table , in which the stable normal conformations in the S 0 state and the twist conformation in the S 1 state are abbreviated as S 0 (N) and S 1 (T), respectively. The dihedral angles of C 4 –C 5 –N 1 –C 6 (around −150°) and C 4 –C 5 –N 1 –H 6 (around −180°) show that the optimized geometries of AYAAQs and AAQ are near planar in the S 0 state, and the distance of H 2 ···O 3 (around 1.8 Å) indicates that the intramolecular hydrogen bond N 1 –H 2 ···O 3 of AYAAQs is relatively weak.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Subsequently, Nagaoka et al studied the ESIPT and 1 O 2 quenching activities of AYAAQs by the static and laser spectroscopic techniques. , Their work demonstrated that the ESIPT positively and linearly correlated with 1 O 2 quenching activities. Recently, Ma and Zheng et al investigated the effects of different substituted groups in intramolecular proton transfer in the S 1 state of AYAAQs by the DFT/TD-DFT/B3LYP level. , Among the previous experimental and theoretical studies, researches mainly focused on the characteristics of excited state fluorescence and the ESIPT reactions of the AYAAQs derivatives. However, their low fluorescence efficiency (Table ) has not been well explained.…”
Section: Introductionmentioning
confidence: 99%